MANAGEMENT STRATEGY OF COASTAL ECOTOURISM IN BALURAN NATIONAL PARK WITH METHOD MULTIDIMENSIONAL SCALING - Daniel M. Rosyid; Nike I Nuzula; Haryo D. Armono (COJ (Coastal and Ocean Journal), 2017)
Coastal resources Baluran National Park (TNB) has been used for coastal marine and ecotourism activities. The increasing number of tourists has led to an increase in tourism activity and related activities. This condition will affect coastal habitat and air quality. This research is intended to embrace the effective management of the ecological, economic, social and institutional dimensions of coastal ecotourism in Baluran National Park. Data analysis using multidimensional scaling method (MDS). The results showed that the effectiveness index of ecotourism management in Baluran National Park is currently in the category quite effective (65.69%). Partially, the ecological dimension (84.15%) is in the effective category, while the social dimension (63.10%), economic dimension (56.46%) and institutional dimension (59.06%) are quite effective. The analysis results show that coastal ecotourism management strategy that implements integrated policy between conservation programs of coastal ecotourism resources, optimization of coastal ecotourism activities based on mangrove, coral reef and culture, increasing comfort among tourists with local communities and increasing provision of coastal ecotourism support infrastructure in the Baluran National Park. Keywords Ecotourism Strategy, Baluran National Park, multidimensional scaling